Foraminiferal and environmental variable data of Idefjorden (2020) sediment surface samples from stations REF, IF20-12, IF20-10, IF20-18, IF20-01 and IF20-04 - Phoebe Alexandra Joy O extquotesingleBrien; Ines Barrenechea Angeles; Kristina Cermakova; Renaud Jarrossay; Irina Polovodova Asteman (PANGAEA, 2025)
The following data file contains the components to a study comparing the ecosystem quality status (EcoQS) assessment using foraminiferal morphospecies and foraminiferal environmental DNA (eDNA) at a historically polluted fjord, located at the Swedish-Norwegian boarder. The data components of the study include foraminiferal count (and sediment volumes), OTU and ASV metabarcoding assemblage and environmental variables (CTD, geochemistry and associated calculated indices) from sediment surface samples taken at 6 stations (REF, IF20-12, IF20-10, IF20-18, IF20-01, IF20-04; the station order corresponds a transect along Idefjorden) using a gemini corer onboard RV Skagerak in November 2020. To obtain the foraminifera count data sediment (stained with Rose Bengal, a solution which causes living tissue to appear pink) was washed through a 63 μm sieve and then picked using a standard stereo-microscope. Only living individuals (indicated by pink stain) were included in the data set. The eDNA analysis was done using a DNeasy® PowerLyzer PowerSoil Kit (QIAGEN), processed using the DADA2 pipeline and the taxonomic assignations were estimated using a sequence bank at ID-Gene ecodiagnostics lab in Geneva Switzerland. The hydrologic environmental parameters were collected using a CTD (Sea-Bird SBE 911; for depth, salinity, conductivity, turbidity, pressure, oxygen, temperature and fluorescence). Heavy metals (As, Cd, Co, Cr, Cu, Hg, Ni, Pb, V and Zn) were analysed at ALS Scandinavia AB using a mass spectrometer and the organic chemistry (δ^1?N, δ^1^3C, TN, TOC and C/N) analysis was conducted at the University of Gothenburg using a SerCon isotope ratio mass spectrometer, both from freeze-dried sediment samples. The environmental variable units are as follows: salinity (PSU), conductivity (S/m), turbidity (NTU), pressure (dbar), oxygen (ml/l), temperature (°C), fluorescence (arbitrary units), metals are all (mg/kg), TN (ppm), TOC (mg/L). C/N, δ^1?N and δ^1^3C have no units as they are isotope ratios.